From victim to survivor : managing the patient with burns - Cross, Pamela J.; American Journal of Nursing Company (New York: American Journal of Nursing Company, 1995)
(Producer) This program serves as a guide for nurses who provide day-to-day care for burn patients. Care during this time period involves wound care management, nutrition, and pain control. Stressing the importance of proper nursing assessment, management, and intervention, this video discusses the importance of wound care, with attention to infection control, including debridement methods, use of the whirlpool, and dressings, as well as alternative methods of wound healing. How to assess a patient's nutritional needs is also covered because the body's response to a burn injury creates a drastic increase in metabolic rate. Also covered is pain control and patient evaluation. Because the psychological damage may be the hardest part of the healing process, this program discusses the seven stages of the psychological recovery process and suggests interventions that lead toward good long-term outcomes
Videocassettes are available at Koleksi Media Perpustakaan HUKM
Keywords: Burns -- nursing